THE USAGE OF STORYTELLING METHOD TO IMPROVE THE STUDENTS' SPEAKING SKILLS - Supriyani Supriyani; Tiansi Meilani; Kunah Kunah (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
Educators need a lot of creativities to make the students interested in learning, especially English which often makes students think it’s difficult subject to learn. Storytelling is one the interesting methods to apply in teaching and learning process. This study aims to make students more active and courageous in expressing themselves in learning English and is also an attempt to determine of effect of using storytelling methods. This research was conducted in class X SMKN 1 Bongas Indramayu with population of 353 students and took sample of 36 students. The writers used the following types of tests: 1). Pre-test. 2). Treatment and 3). Post-test. This research is to answer questions; 1). How is the speaking ability of the students? 2). How is the fluency of students’ speaking skills? And 3) How is the use of the storytelling method in improving students’ speaking skills at SMKN 1 Bongas Indramayu? This study uses quantitative method. The population in this study was 353 and a sample of 36 students was taken from class 10. From this research, there are good results of using storytelling method in improving students’ speaking skills